Faecal examination and PCR to detect Strongyloides venezuelensis in experimentally infected Lewis rats - Marra, Nelson Mendes; Chiuso-Minicucci, Fernanda [UNESP]; Machado, Gabriel Capella; Zorzella-Pezavento, Sofia Fernanda Gonçalves [UNESP]; França, Thaís Graziela Donegá [UNESP]; Ishikawa, Larissa Lumi Watanabe [UNESP]; Amarante, Alessandro Francisco Talamini do [UNESP]; Sartori, Alexandrina [UNESP]; Amarante, Mônica RV (Instituto Oswaldo Cruz, Ministério da Saúde, 2010)
More sensitive methodologies are necessary to improve strongyloidiasis diagnosis. This study compared the sensitivities of the McMaster modified technique and polymerase chain reaction (PCR) assays, both performed in faecal samples. Lewis rats were subcutaneously infected with 4,000, 400 or 40 infective third-stage larvae, considered as high, moderate or low infection, respectively. Seven days later, they were euthanized to count adult nematodes recovered from the small intestine. Stool samples were used to count the number of eggs per gram (EPG) of faeces and to detect parasite DNA by PCR performed with a species and a genus primer pair. The sensitivity of these assays depended upon parasite burden and the primer specificity. All assays presented 100% sensitivity at the highest parasite load. In the moderate infection, EPG and PCR with the genus primer maintained 100% specificity, whereas PCR sensitivity with the species primer decreased to 77.7%. In low infection, the sensitivity was 60% for EPG, 0% for PCR with the species primer and 90% for PCR done with the genus primer. Together, these results suggest that PCR with a genus primer can be a very sensitive methodology to detect Strongyloides venezuelensisin faeces of Lewis rats infected with very low parasite burden.
Keywords: Strongyloides venezuelensis; faecal egg counts; DNA; PCR; diagnosis; Lewis rats